Seeds and stems - Hanselmann, Simon 1981- (Fantagraphics Books Inc., 2022)
"Simon Hanselmann has established himself as one of the first rank storytellers of our time with his four graphic novels about the funny and poignant lives of roommates Megg, Mogg and Owl -- stories which combine raunchy stoner comedy with exceptional pathos and insight into the human condition. Seeds and Stems collects all of Hanselmann's work that never made it into his bestselling books -- rare and often experimental Megg and Mogg adventures originally published in self-published, limited-edition zines produced between 2016-2019, along with a generous smattering of rarities from various anthologies and magazines. This collection is designed and curated entirely by the artist. To capture the authentically seedy look of a prescription bottle, Hanselmann's hand-painted cover is wrapped in a transparent orange acetate jacket."--Publisher description
Keywords: Hexe; Drogenabhängigkeit; Werwolf; Depression; Eulen; Katze; Witches / Comic books, strips, etc; Cats / Comic books, strips, etc; Owls / Comic books, strips, etc; Werewolves / Comic books, strips, etc; Drug addicts / Comic books, strips, etc; Depressed persons / Comic books, strips, etc; Comic